2021
DOI: 10.1111/hsc.13330
|View full text |Cite
|
Sign up to set email alerts
|

Well‐being losses by providing informal care to elderly people: Evidence from 310 caregivers in Shanghai, China

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, there are some obvious differences between financial support and informal care provision. Taking care of parents, especially who come with poor physical conditions, requires more time, energies and patience from their adult children, which made negative influence on the physical condition, income and leisure of adult children [29,30]. Compared with informal care provision, financial support is easier to perform under the background of the shrink in family size, frequent population mobility, increasingly fierce labor market competition and improved accessibility of formal care services [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some obvious differences between financial support and informal care provision. Taking care of parents, especially who come with poor physical conditions, requires more time, energies and patience from their adult children, which made negative influence on the physical condition, income and leisure of adult children [29,30]. Compared with informal care provision, financial support is easier to perform under the background of the shrink in family size, frequent population mobility, increasingly fierce labor market competition and improved accessibility of formal care services [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Liu (2021) Family carers expressed unmet need concerning information in a study by Rosa et al (2010) of 112 caregivers of patients affected by moderate to severe dementia. However, the authors found a high incidence of family members who still expressed the need for additional information and support from formal networks about the illness (Rosa et al, 2010).…”
Section: Support To Carementioning
confidence: 99%